Growth and Development of Mouse Secondary Spermatocytes (Mouse muscle) After Giving Extra Kepel Fruit (Stelechocarpus burahol) - Merta, I Wayan; Kusmiyati, Kusmiyati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Indonesia has a tropical climate is rich in flora diversity. Many medicinal plants, including the Kepel (Stelechocarpus burahol), are herbal medicines. Kepel Fruit (Stelechocarpus burahol) contains secondary metabolites of alkaloids, flavonoids, polyphenols, saponins, triterpenoids and quinones. Some of these compounds have anti-fertility properties. Antifertility compounds are compounds that can prevent fertility by interfering with several normal reproductive mechanisms, both in men and women. This study aims to analyze the effectiveness of Kepel fruit extract on the growth and development of secondary spermatocytes in mice (Mouse muscle). This research uses true experiments and Posttest-Only Control with a quantitative approach. The samples used for this research design, both experimental and controlled, were taken randomly. Testing the significance of the treatment effect uses parametric statistics, namely the One-Way ANOVA test at a significance level of 5% (α = 0.05). Then, if there are differences, continue with the LSD further test (Least Significant Difference) at a significance level of 5% (α = 0.05). This research design used a Randomized Block Design (RAK) with a total sample of 32 mice (Mouse muscle) with 8 repetitions and 3 treatment groups. The growth and development of secondary spermatocytes in mice are determined by counting the number of secondary spermatocytes in the seminiferous tubules of mouse testicular incisions. The results of the one-way Anova test show that the calculated F is 6.41, and the value is sig. (P.Value) of 0.002, these results suggest P.Value (0.002) < the α value (0.05), which means that the number of secondary spermatocytes is significantly different in each group so that this study can conclude that the administration of Kepel fruit extract (Stelechocarpus burahol) can significantly reduce the number of growth and development of mouse secondary spermatocytes (Mouse muscle ).